2020
DOI: 10.1371/journal.pone.0239678
|View full text |Cite
|
Sign up to set email alerts
|

Power-law population heterogeneity governs epidemic waves

Abstract: We generalize the Susceptible-Infected-Removed (SIR) model for epidemics to take into account generic effects of heterogeneity in the degree of susceptibility to infection in the population. We introduce a single new parameter corresponding to a power-law exponent of the susceptibility distribution at small susceptibilities. We find that for this class of distributions the gamma distribution is the attractor of the dynamics. This allows us to identify generic effects of population heterogeneity in a model as s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 29 publications
(57 reference statements)
3
42
0
Order By: Relevance
“…The same result has also been recently obtained in Ref. (47). Note however that the full quasi-homogeneous description of the epidemic dynamics requires both R e ( S ) and S e ( S ), that in a general case a characterized by different scaling exponents.…”
Section: Theory Of Epidemics In Populations With Persistent Heterogensupporting
confidence: 89%
“…The same result has also been recently obtained in Ref. (47). Note however that the full quasi-homogeneous description of the epidemic dynamics requires both R e ( S ) and S e ( S ), that in a general case a characterized by different scaling exponents.…”
Section: Theory Of Epidemics In Populations With Persistent Heterogensupporting
confidence: 89%
“…Early computer modelling indicated that mandated lockdown would be highly effective and prevent hundreds of thousands of deaths. [4] However, the homogenous models used to produce counterfactual curves have been criticized in many papers, since heterogeneity in susceptibility, activity, infectivity, and compliance all tend to flatten curves by themselves relative to counterfactual homogeneous populations [6]- [8], [10], [12]. To the extent that test-driven infection control or voluntary compliance do not fully explain our data, our results are consistent with this criticism and with country-comparison studies showing smaller direct effects of full lockdown itself [16].…”
Section: Discussionmentioning
confidence: 99%
“…We assume persistent levels of social activity α i to also follow a Gamma distribution with dispersion parameter κ . In several recent studies of epidemic dynamics in populations with persistent heterogeneity [15, 17, 52] it has been demonstrated that dispersion parameter κ determines the herd immunity threshold. Multiple studies [10, 48, 53] of real-world contact networks report an approximately exponential distribution of α , which corresponds to κ 1.…”
mentioning
confidence: 99%